Influence of non-metallic inclusions on fatigue life in the very high cycle fatigue regime. (March 2016) - Krewerth, D.; Lippmann, T.; Weidner, A.; Biermann, H.
Highlights: The applied variants of active, reactive and functionalized filters for metal melt filtration of the steel 42CrMo4 (AISI 4140) showed similar effects on the fatigue behavior in the very high cycle fatigue. For all variants large scatter of the fatigue life was observed. The functionalized Al2 O3 –C filter coated with mullite showed lower fatigue lives compared to the other variants. The dominant failure type in the investigated cast steel AISI 4140 after hot-isostatic pressing are clusters of endogenous (primary, secondary) non-metallic inclusions mainly of the alumina-type. Four different internal crack initiation types were clearly identified in the very high cycle fatigue by plotting (i) the radii of the fisheyes and (ii) the inclusion depth versus the fatigue life. Both, the radius of the fisheye and the inclusion depth decreases with increasing number of cycles to failure. Abstract: The present paper deals with the influence of non-metallic inclusions on fatigue life in the high cycle fatigue and the very high cycle fatigue regime. For that purpose, several castings of steel 42CrMo4 (AISI 4140, DIN EN 1.7225) were produced by using recently developed novel metal-melt filters. The specimens were tested in hot-isostatically pressed and heat treated condition. After fatigue failure every fracture surface was intensively investigated by scanning electron microscopy in order to define the type, the size, the chemical composition, the morphology and the location of the crack initiating discontinuity. Subsequently, Murakami's √ area model was used for the evaluation of the influence of non-metallic inclusions on the fatigue life. In the present investigation four common types of chemical compositions of crack initiating discontinuities were identified. Furthermore, four different internal failure types and their influence on the fatigue life in cast steel were investigated and described. Thus, the present contribution proposes a basic correlation determined from fatigue lives in case of various internal crack initiation types. The key parameters for fatigue life prediction in case of internal fatigue failure in the very high cycle fatigue regime are (i) the size of the crack initiating discontinuity, (ii) the inclusion depth and (iii) the crack initiating failure type.